Resilience relationship with effort-reward imbalance mediated by teaching emotions in elementary teachers of Taft City - Fatemeh Jannesar; Ahmad Zandvanian Naeini; Hossain Hassani (طب کار)
Introduction:  The imbalance between reward and effort, characterized by the disparity between effort put in and rewards received, can be greatly affected by personal abilities and feelings.  The present study aimed to investigate the relationship of resilience with Reward-Effort imbalance mediated by teaching emotions in elementary school teachers of Taft City. Materials and Methods: The methodology used in the research was correlational along with structural equation modeling. The statistical population included all elementary school teachers in Taft City during the academic year 2020-2023, totaling 679 individuals. A sample size of 250 participants was determined, and the sampling was conducted on a voluntarily basis. The research tools included the Connor and Davidson Resilience Questionnaire (2003), Reward-Effort Imbalance (Siegrist, 2010), and Teaching Emotions (Villavicencio, 2010). Finally, data from 234 participants were analyzed using structural equation modeling through SPSS26 and AMOS24 software. Results: The results showed that the direct effect of resilience on Reward-Effort imbalance was significant (β=0.180; P=0.029); moreover, the direct effect of resilience on teaching emotions was notable (β=0.396; P=0.001); And the direct effect of teaching emotions on Reward-Effort imbalance is also significant (p=0.211; P=0.018);  additionally, the results showed that the indirect effect of resilience on Reward-Effort imbalance through the mediating influence of teaching emotions was significant (β=0.083; P=0.011) and the total effect was also significant (βt =0.264, P=0.001). Conclusion: In conclusion, focusing on teaching emotions within resilience training programs for elementary school teachers may help reduce Reward-Effort imbalance by regulating emotions.